Presentation and Outcomes of Patients with ESKD and COVID-19 - Valeri, Anthony M; Robbins-Juarez, Shelief Y; Stevens, Jacob S; Ahn, Wooin; Rao, Maya K; Radhakrishnan, Jai; Gharavi, Ali G; Mohan, Sumit; Husain, S Ali (Journal of the American Society of Nephrology, 2020)
The relative immunosuppression and high prevalence of comorbidities in patients with ESKD on dialysis raise concerns that they may have an elevated risk of severe coronavirus disease 2019 (COVID-19), but outcomes for COVID-19 in such patients are unclear. To examine presentation and outcomes of COVID-19 in patients with ESKD on dialysis, we retrospectively collected clinical data on 59 patients on dialysis who were hospitalized with COVID-19. We used Wilcoxon rank sum and Fischer exact tests to compare patients who died versus those still living. Two of the study's 59 patients were on peritoneal dialysis, and 57 were on hemodialysis. Median age was 63 years, with high prevalence of hypertension (98%) and diabetes (69%). Patients who died were significantly older than those still living (median age, 75 versus 62 years) and had a higher median Charlson comorbidity index (8 versus 7). The most common presenting symptoms were fever (49%) and cough (39%); initial radiographs most commonly showed multifocal or bilateral opacities (59%). By end of follow-up, 18 patients (31%) died a median 6 days after hospitalization, including 75% of patients who required mechanical ventilation. Eleven of those who died had advanced directives against intubation. The remaining 41 patients (69%) were discharged home a median 8 days after admission. The median initial white blood cell count was significantly higher in patients who died compared with those still living (7.5 versus 5.7×10 / l), as was C-reactive protein (163 versus 80 mg/L). The association of COVID-19 with high mortality in patients with ESKD on dialysis reinforces the need to take appropriate infection control measures to prevent COVID-19 spread in this vulnerable population.